Exploring Lecturers’ Responsiveness to Teaching and Learning Using Moodle at a Namibian University - Bock, Jacqueline TC; van Wyk, Micheal M (Research in Social Sciences and Technology- OpenED Network, 2025)
The responsiveness of lecturers at Namibian universities to Moodle as a teaching and learning platform is addressed in this paper. It observes, among other things, the increasing adoption of Moodle as an LMS in Namibian and higher education settings globally and notes that special challenges may be barring Namibian universities from harnessing Moodle to full potential; chief among these are issues concerning poor internet connectivity and limited technical support. Guided by the interpretative paradigm and anchored in the Community of Inquiry (CoI) framework, a robust and widely respected research methodology, the study explored lecturers' responsiveness to teaching and learning using Moodle at a Namibian university. The research employs a descriptive case study design and involves a purposive sample of seven faculty members from diverse disciplines. In-depth virtual interviews were used for data collection, with thematic analysis revealing key findings. Findings revealed various factors influencing lecturer responsiveness, including factors promoting blended learning and challenges hindering responsiveness. Further challenges encompass workload, course design, technical support availability, and access to learning resources. Based on the results, implications advocated for comprehensive Moodle orientation and training programmes, improved technical support, reliable internet access, and staff well-being. This research provides valuable insights for enhancing e-learning practises at a Namibian higher education institution. Future research may investigate the pedagogical aspects of Moodle usage in other contexts and extend these insights to diverse educational settings.